Use of Tannin-Containing Plants as Antimicrobials Influencing the Animal Health - Dakheel, Mohammed M; Al-Mnaser, Afnan A; Quijada, Jessica; Woodward, Martin J; Rymer, Caroline (The Iraqi Journal of Veterinary Medicine, 2021)
The antimicrobial effects of diverse tannin-containing plants, particularly condensed tannins (CTs) produced from various plants, are the subject of this study. CT components can be determined using CT-specific procedures such the HCl-Butanol Acetone assay, Thiolysis reaction, and HPLC/MS analysis. These methods indicate CT contents, including mean degree of polymerization, the procyanidins and prodelphinidins ratio (PC/PD%), the isomers of trans- and cis-, and CT concentration. Tannin-containing plants possess antibacterial action, which can be attributed to their protein linkage technique, and tannin-type variations, particularly CTs extract and their PC/PD%. The effects of CT components on the development of Gram-positive and Gram-negative bacteria have been documented for their relative PC/PD%; this is regarded to be a key predictor of tannin characteristics in terms of antimicrobials. In conclusion, tannins, more specific CT compositions, have significant impacts on in vivo trials of animal productions and utilization of metabolites and fermentation in vitro experiments. These findings need further investigations to fully understand how CT-types act on animal feeding in terms of enhanced nutritional quality of animal diets, which may have implications for human and animal health.